Disturbios da comunicacao em criancas de alto risco neonatal - Tamashiro, I. A. [UNESP]; Nascimento, L. T. [UNESP]; Martins, Regina Helena Garcia [UNESP] (My University, 1997)
Neonatal high risk children present high incidence for communication disorders and delay development of language. The present study aimed to evaluate the incidence of communication disorders and long term follow up of neonatal high risk children. Twenty-one children were followed up to age of four years old and were evaluated for the development of linguistics aspects. The main high risk neonatal factors were: prematurity, mechanical ventilation, long time in the incubator and severe hypoxia. In 47,62% of the cases, the following communication disorder were found: articulation disorders (9,52%), simple (9,52%) and small and (14,29%) with delay development of language. The incidence of these disorders was greater among male children (57,14%).
Disorders of communication in high-risk newborn infants
Keywords: Comunication disorders; Neonatal high risk; artificial ventilation; clinical article; communication disorder; controlled study; female; follow up; high risk patient; human; incubator; language development; male; newborn; newborn hypoxia; prematurity; preschool child